2020
DOI: 10.3390/mi11040403
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of the Flow and Heat Transfer Characteristics in Microchannel Heat Exchangers with Reentrant Cavities

Abstract: The application of microchannel heat exchangers is of great significance in industrial fields due to their advantages of miniaturized scale, large surface-area-to-volume ratio, and high heat transfer rate. In this study, microchannel heat exchangers with and without fan-shaped reentrant cavities were designed and manufactured, and experiments were conducted to investigate the flow and heat-transfer characteristics. The impact rising from the radius of reentrant cavities, as well as the Reynolds number on the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Tuckerman and Pease [ 103 ] were the pioneering researchers who proposed microchannel heat exchangers. Researchers [ 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 ] examined the various cavity forms in microchannel heat exchangers. The cavity increases the heat transfer area, enhances mainstream disturbance, and causes chaotic advection, substantially affecting heat-transfer enhancements.…”
Section: Effect Of Cavities In Microchannel Heat Exchangersmentioning
confidence: 99%
“…Tuckerman and Pease [ 103 ] were the pioneering researchers who proposed microchannel heat exchangers. Researchers [ 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 ] examined the various cavity forms in microchannel heat exchangers. The cavity increases the heat transfer area, enhances mainstream disturbance, and causes chaotic advection, substantially affecting heat-transfer enhancements.…”
Section: Effect Of Cavities In Microchannel Heat Exchangersmentioning
confidence: 99%
“…Eneren et al [26] presented a comprehensive review of various experimental studies and addressed different nanofluid parameters such as thermal conductivity, stability, and particle-surface interactions such as erosion, abrasion, corrosion, and particle clumping that could hinder the heat transfer rate in microchannels. Huang et al [27] carried out an experimental analysis of heat transfer and fluid flow properties in microchannel heat exchangers with fan-shaped cavities. To compare the advantages of fan-shaped cavities, conventional microchannel heat exchangers were also tested in similar conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The main advantage of microdevices is that these offer a rapid, portable, simple, and low-cost tool [9]. For instance, Huang et al [10] developed an experimental work for a microchannel heat transfer, where it was concluded that reentrant cavities are an ideal approach to improve the performance. In their work and review was outlined that to include elements to perturb the flow enhances heat transfer in microchannels.…”
Section: Introductionmentioning
confidence: 99%